(untitled) (Eurasian Journal of History, Geography and Economics, 2024)
The article deals with current problems of occupational risks estimation in social insurance and key notions in the estimation methods, and substantiates the necessity of using occupational risks estimation methods in social insurance. The author proposes a new technique of occupational risks estimation, and determines factors that influence the level and scale of occupational risks. According to the current legislation, the creation of a labor protection management system, which includes occupational risk management, is the responsibility of every Uzbek employer. In addition, such measures increase the security of the business as a whole and allow employees to properly organize social insurance.